Effects of the Latest LRFD Block Shear Code Change - Epstein, Howard I. (Engineering Journal, 1996)
This paper examines the effects of the required change in the use of the block shear design strength equations resulting from the latest AISC-LRFD code treatment. The latest code either gives the same results as the previous code or is more conservative. The parameters of the connections for which the two treatments differ are presented, as well as the percentages of the differences. On the basis of recently reported experimental results, the need for further refinement of the codes is presented.